Analysis Effect of Duct Length– Nozzle Diameter Ratio and Tip Clearance Variation on the Performance of K-Series Propeller - Arief, Irfan Syarif; Musriyadi, Tony Bambang; Mafera, Ahmad Dwi Arta Je (International Journal of Marine Engineering Innovation and Research, 2025)
One type of ship propeller is a ducted propeller. Ducted propellers are propellers with sheath or duct that can increase thrust on the propeller and useful for directing the flow of water that will pass through the Propeller. In addition to improving thrust, ducted propellers can also increase torque compared with no duct. The basic theory of momentum for this ducted propeller operation has been used by Horn (1940). In order for the efficiency of the thrust to be of good value, the volume of water passing through the propeller should be as large as possible, with the smallest possible flow velocity. The most important components of ducted propeller are Ld / D and tip clearance. Ld / D is a coefficient comparison between the length of the casing / duct and the diameter of the duct, while the tip clearance is the distance between the tip of the propeller with an inner diameter of the duct. Both components are discussed in this study. The purpose of this research is to know the performance of propeller after given variation on Ld / D and tip clearance. The method used for propeller analysis is Computational Fluid Dynamic (CFD). Based on simulation result, the most optimal propeller performance is ducted propeller with Ld / D = 0.5 and tip clearance 40 mm.